Erosion Expert System for Environmental Impact Assessment - Foo, Yeong Seng (1998)
Soil Erosion is one of the most important natural resources management problems in the world. It is a primary source of sediment that pollutes streams and fills reservoirs. Development especially in hilly terrain will significantly increase this process and cause adverse impact to the local and regional environment. The main purpose of the Erosion Expert System (EES) being developed was to help EIA consultants in preparing the Erosion part of EIA reports besides providing relevant information on erosion. Computer programs developed can help in information retrieval and decision support when dealing with erosion control. The rule-bases of the system was developed using CLIPS version 6.04, an Expert System Shell which was designed by NASA (National Aeronautics and Space Administration). The Graphic User Interface (GUI) for the system was designed by using Visual Basic 5. Results show that Knowledge-based system would be useful especially if the domain knowledge is systematic. The advantage of Knowledge-based system is that it leads to a greater degree of unification in preparing EIA reports but it should be used only as an alternative source of knowledge since human specialist would be a preferred approach in environmental planning.